Effects of organic fruit juices on physicochemical, microbiological, and antioxidative aspects of fermented whey beverages from organic goat and cow milk, produced at laboratory and industrial scales - J.O. Szafrańska; R. Waraczewski; M. Bartoń; M. Wesołowska-Trojanowska; W. Maziejuk; P. Nowak; B.G. Sołowiej (Journal of Dairy Science, 2024)
ABSTRACT: Fermented milk beverages have been known for years and are characterized by excellent health-promoting properties. Therefore, consumer attention has been drawn to this product type in recent years. In the presented research, the technology of production in laboratory and industrial scales of controlled fermentation of whey beverages containing sweet or sour organic cow or goat whey, with the addition of organic fruit juices (apple, blackcurrant, or Kamchatka berry juice), are described. Food production on a laboratory scale involves small-batch processes designed for experimentation and refinement, often with precise control over variables and conditions. In contrast, industrial-scale food production in enterprises focuses on large-volume output with an emphasis on efficiency, consistency, and adherence to regulatory standards for mass consumption. This study examined the amino acid content and nutritional value of the obtained products. Tests were carried out on fermented whey drinks' microbiology and antioxidant properties. Significance was determined using ANOVA; each prepared drink was characterized by better antioxidant properties and nutritional values compared with products without juice addition. Microbiological examination proved that only 1 product was not fit for consumption according to the Polish norm. Using whey (goat or cow) as a base for a fermented beverage with enhanced health benefits is a positive step toward using products commonly regarded as waste.